Implementasi Kriptografi Untuk Mengamankan Database Administrasi Menggunakan Metode CAESAR CIPHER dan BASE64 - Syakur Nurokhman; Jaka Sutrisna (CV. Multi Kreasi Media, 2022)
The development of information technology has now experienced very rapid advances in communicating, accessing data or information through various media, one of which is through website media on the internet. Security in the storage of data or information is very important. Pt. Pegadaian are worried that if they will use the application, it is not safe and when stored in a database, because data and information are important and are still vulnerable to theft and misuse by certain parties which can cause huge losses. In designing this application, the author created a method by means of an encryption process. Caesar Cipher cryptography uses number keys to encrypt and Base64 systems to represent byte data as ASCII characters.